Transition to agricultural market economies : the future of Kazakhstan, Russia, and Ukraine - Schmitz, Andrew; Meyers, William H. 1941- (CABI, 2015)
This book offers information on the agricultural economy of Kazakhstan, Russia and Ukraine (KRU region). It covers a wide range of relevant issues, such as agricultural policies that affect production and trade, the privatization of land markets, the optimal use of fertilizers and other inputs, and the role of cooperatives. A number of sectors are examined, including poultry, dairy, fruits, and vegetables. However, particular attention is paid to the potential expansion of the region's grain sector and why the KRU region emerged during the 2000s as a major grain exporter, and its potential to further expand grain production and exports. The authors of the book's 23 chapters include scholars from Europe, the USA and Canada who are working with collaborators in the KRU countries. By broadening the knowledge and understanding of the constraints, potentials and policy trade-offs that will determine the agricultural development and trade performance of the KRU countries, this book serves as an important resource for global stakeholders focused on food security and food markets and for the scholarly community that analyses the workings and evolution of these markets.